PDS and community schools : the nexus of practice - Ferrara, JoAnne, 1955- (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2022)
"How the Professional Development School and Community School strategy might benefit from an integrated perspective serves as the guiding framework for this volume of "Research in Professional Development Schools". This book advocates for blending these two approaches to address the needs of P-20 settings and their communities. Because we recognize the inherent strengths in both models, we encouraged chapters that had as a primary focus one or both models as they sought to support teacher preparation and K-12 partners. Subsequently, a series of questions framed the conversation around the potential for combining these models as well as what such an integrated model might present for teacher education programs, K-12 partners, and their communities. Since this volume explores three different aspects of the relationship between Professional Development Schools and Community Schools, a set of guiding questions were offered to guide the specific models addressed"-- Provided by publisher.
Keywords: Laboratory schools -- United States.; Community schools -- United States.; Community and school -- United States.; Teachers -- Training of -- United States.; Educational change -- United States.; Education -- Teacher Training & Certification.; Educational strategies and policy.; Teacher training.; elektronické knihy; electronic books